Automação de seleção e quantificação de itens em notas de empenho no sistema AFI/SEFAZ-AM - Gomes, Afonso dos Santos (Brasil, 2024)
This document describes the development of a computational application designed to automate the selection and quantification of items in purchase orders within the AFI/SEFAZ-AM System issued by SEDUC-AM. The application aims to significantly reduce the time spent on item selection during the issuance of purchase orders. Manually issuing orders containing more than 450 items took approximately 6 hours, while the developed application reduced this time to approximately 10 minutes. This time savings is achieved through intuitive on-screen interactions, integration with Excel spreadsheets, and automated insertion into the HTML table of the AFI/SEFAZ-AM System. The application was implemented using the Python programming language, along with key libraries such as Playwright for Firefox browser automation, openpyxl for accessing Microsoft Excel files, and PySimpleGui for creating simple yet effective user interfaces.